Overweight, obesity and female sexuality in perimenopause: a preliminary report - Jarząbek-Bielecka, Grażyna; Wilczak, Maciej; Potasińska-Sobkowska, Anna; Pisarska-Krawczyk, Magdalena; Mizgier, Małgorzata; Andrzejak, Karolina; Kędzia, Witold; Sajdak, Stefan (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: The research was conducted among patients of the Department of Perinatology and Gynaecology of the Poznań University of Medical Sciences. Its aim was to investigate the influence of overweight and obesity on female sexuality during the perimenopausal period. Preliminary results of the research are presented in the thesis, which was as a matter of fact intended as a preliminary report. The examination of sexual functions of the patients was performed with the use of the Female Sexual Function Index (FSFI) form. Material and methods: Sixty-one women during the perimenopausal period filled out the survey, with the average age of these women being 51 years. Forty-two of the examined women had an appropriate body mass index (BMI), i.e. between 18.5 and 25, while for 19 of the women, the BMI was above normal. For statistical analysis and in order to assess the differences between the two above-mentioned groups of patients, the nonparametric Mann-Whitney test was applied. A statistically significant value was assumed at p < 0.05. The results of the conducted research indicated no such difference between the women with differing BMI for the specific domains of the FSFI test. Results: The results obtained show that research in the area needs to be continued. Conclusions: All the hitherto existing scientific studies also seem to indicate that the influence of overweight and obesity on female sexuality during the perimenopause has not yet been unambiguously proven. Beyond any doubt, however, sexual disorders appear in women at this time of life and the factors which determine them can vary greatly. Given the character of the situation, women ought to be supported both by a team of specialists representing different branches of medicine as well as by their relatives. The whole situation also calls for more research of the important subject matter.